Modelling the Quality Aspects of Internet Commerce with Customers’ Shopping Experiences - Sulong, Muhammad Suhaizan; Abdul-Aziz, Azlianor; Wongsim, Manirath (2010)
The growth of the World Wide Web gave birth to online businesses and with rapid changes in web technologies, Internet commerce is expected to grow. Despite the growth, many online businesses have failed. Thus, the quality aspects in developing Internet commerce application are very important issues to the success of customers experience initiatives. This review paper analyses the relevant literature on the aspects of quality in Internet commerce in relation to customers' behaviour. The analysis results reveal that the key aspects of quality are system quality, information quality and service quality which have strong effect on customers' behaviour - trust, satisfaction and loyalty. The importance of quality in Internet commerce needs to be valued and accepted in order to mature and improve the electronic service online for customers.